Application of matlab-based interface for the control of microbioreactor operation - Zainal Alam, Muhd. Nazrul Hisham (Penerbit UTM Press, 2018)
This work presents the use of Arduino-based embedded system interfaced to MATLAB software packages as an alternative cost-effective solution for the control of the microbioreactor operation. In the presented work, a microbioreactor platform with a working volume of approximately 1.5 mL have been fabricated using a low-cost poly (methylmethacrylate) (PMMA) and poly(dimethylsiloxane) (PDMS) polymers. The reactor have been integrated with stirring control, fuzzy logic temperature control, and aeration feature via a miniature air compressor. Control program of the microbioreactor system was established using Simulink, MATLAB software were executed by interfacing the program with Arduino Mega 2560 microcontroller for input and output of signals. Numbers of experimentation were performed to validate and demonstrate the potential of the proposed method. Satisfactorily degree of control and supervision was achieved (± 1-3% of the set-point values). The entire microbioreactor system can be operated stably for a least 48 hours. The work demonstrated the usefulness of MATLAB software in establishing a microbioreactor operating interface that consisted merely few Simulink program block sets and executed on a low-cost Arduino board.